Big Book Media on Beginning Reading Skills of Grade 2 Elementary School Students: Media Big Book Terhadap Keterampilan Membaca Permulaan Siswa Kelas 2 Sekolah Dasar - Andriani, Titalia; Nuroh, Ermawati Zulikhatin (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of Big Book media on the early reading skills of second grade students of SD Hafidz Al Qur'an Porong. This research uses quantitative research. The method used is a pre-experimental design method with a research design of One Group Pretest -Posttest . The sample in this study was the second grade students of SD Hafidz Al Qur'an Porong, totaling 18 students using a saturated sample. The data collection in this study used a test (Pretest and Posttest ) on initial reading skills. The results showed that there was an effect of Big Book media on the reading skills of second grade students of SD Hafidz Al Qur'an. This is evidenced by the results of the calculation of the hypothesis test with a level of a = 0.05 or 5% meaning 0.000 <0.05 then Ho is rejected and Ha is accepted. So that learning using Big Book media will show differences, it can be shown that there is an effect of Big Book media on early reading skills of second grade students of SD Hafidz Al Qur'an Porong. The magnitude of the effect in this study was calculated using the eta squared test and obtained the results of 1.04 > 0.14 which indicated the criteria for a large influence. So it can be concluded that the Big Book media has a big influence on the reading skills of elementary school students in grade II